0.25-0.03(x+2)=0.02(3-x)

Simple and best practice solution for 0.25-0.03(x+2)=0.02(3-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.25-0.03(x+2)=0.02(3-x) equation:


Simplifying
0.25 + -0.03(x + 2) = 0.02(3 + -1x)

Reorder the terms:
0.25 + -0.03(2 + x) = 0.02(3 + -1x)
0.25 + (2 * -0.03 + x * -0.03) = 0.02(3 + -1x)
0.25 + (-0.06 + -0.03x) = 0.02(3 + -1x)

Combine like terms: 0.25 + -0.06 = 0.19
0.19 + -0.03x = 0.02(3 + -1x)
0.19 + -0.03x = (3 * 0.02 + -1x * 0.02)
0.19 + -0.03x = (0.06 + -0.02x)

Solving
0.19 + -0.03x = 0.06 + -0.02x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.02x' to each side of the equation.
0.19 + -0.03x + 0.02x = 0.06 + -0.02x + 0.02x

Combine like terms: -0.03x + 0.02x = -0.01x
0.19 + -0.01x = 0.06 + -0.02x + 0.02x

Combine like terms: -0.02x + 0.02x = 0.00
0.19 + -0.01x = 0.06 + 0.00
0.19 + -0.01x = 0.06

Add '-0.19' to each side of the equation.
0.19 + -0.19 + -0.01x = 0.06 + -0.19

Combine like terms: 0.19 + -0.19 = 0.00
0.00 + -0.01x = 0.06 + -0.19
-0.01x = 0.06 + -0.19

Combine like terms: 0.06 + -0.19 = -0.13
-0.01x = -0.13

Divide each side by '-0.01'.
x = 13

Simplifying
x = 13

See similar equations:

| 995=6x+x^2 | | 16x-8=.5(110+2x) | | 2x-43=64358 | | 3/9-5/9=2/9-8x/9 | | 18//.04 | | t^2-14t-22=0 | | (3a-4)(2a+5)= | | 55.96=Pi*r*8.5 | | 8y+3(y-4)=3(y+1)-2 | | log(6)(216)=3x+1 | | 4X^2y^6+36x^4y^3=0 | | n^2*4n-1=0 | | 2(4x+5)+14= | | t^2-6t-18=0 | | -4.9x^2+19.6+0=14.7 | | 1x+3y=326 | | 0.02(y-5)+0.16y=0.06y-0.7 | | 4y*5= | | 16-4d=2 | | 350/.8= | | 2+2(2-x)=5+3(x+4) | | 4x-4x+7y-3y+x= | | 350=.8x | | 0.17(0.2+x)=(0.3-x)(0.3-x) | | 8x^2-6x-26=-2x^2-9x | | 0.17(0.5-x)=(0.1+x)(0.1+x) | | f(72)=-2(72)+23 | | (m^2+9)=0 | | 5+2(x-1)-3(1-x)=4+5(2x-3) | | 2t^2-20t-60=0 | | g(5)=12 | | (x+18)+4=x+(18+4) |

Equations solver categories